2022
DOI: 10.1186/s12886-022-02460-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and visual prognostic factors in congenital aniridia

Abstract: Background Evaluate outcomes and identify prognostic factors in congenital aniridia. Methods Retrospective interventional case series of patients with congenital aniridia treated between 2012–2020. Ocular examination and surgical details were collected. Surgical failure was defined as disease progression or need for additional surgery for same/related indication. Kaplan–Meier survival curves, Wilcoxon test, and univariate and multivariate linear re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…GDD implants were the main choice of procedure and presented the best success rate (71%) (mean follow-up period: 14.2 ± 15.4 years). This study showed a better success rate of BGI (74%) compared to AGV (63%), but the latter presented less tube revision (62) .…”
Section: Indicationsmentioning
confidence: 54%
See 2 more Smart Citations
“…GDD implants were the main choice of procedure and presented the best success rate (71%) (mean follow-up period: 14.2 ± 15.4 years). This study showed a better success rate of BGI (74%) compared to AGV (63%), but the latter presented less tube revision (62) .…”
Section: Indicationsmentioning
confidence: 54%
“…In most studies, GDD was used after failure of the primary surgical approach (goniotomy or trabeculotomy). However, GDDs were employed as the first-line treatment in some cases in which angle surgeries have a high risk of failure, such as phakomatosis (59) , aphakic glaucoma (60,61) and aniridia (35,62) . Chen et al (13) evaluated AGV implanted as the first surgical approach in patients with PCG or JOAG (age <18 years), uveitic glaucoma, or secondary glaucoma.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, they found that glaucoma drainage devices exhibited the highest success rate (71%) in controlling IOP over a long-term follow-up. 24 Chang et al also identified nystagmus and ocular hypertension as important prognostic factors for poor visual outcome in aniridia. Notably, they found a high rate of secondary ocular hypertension following cataract surgery, emphasizing the need for careful management.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobson, Mian, and Bohnsack found a higher proportion of aniridia patients with legal blindness at presentation (38%), perhaps due to inclusion of WAGR subjects and more heterogeneous mutations of PAX6 in their subjects. 27 Our subjects with PAX6 deletions associated with WAGR spectrum disorder had worse visual efficiency values than aniridia subjects with nonsense mutations, with the majority of the Limitations of this study include potential for investigator bias in selection and review of subjects, which is a general problem in retrospective studies and was likely reduced by de-personalizing the data. The search of electronic records may not have identified all eligible subjects, and the number of patients may not have been sufficiently large to detect all differences between groups.…”
mentioning
confidence: 88%